WASHBACK EFFECT OF THE CLASSROOM TEST IN JUNIOR HIGH SCHOOL - Maria Tirtaningrum; Agustinus Ngadiman (Magister Scientiae, 2015)
This study focused on the washback effects of classroom tests administered in Junior High School in Indonesian EFL contexts. To obtain the expected data two sets of questionnaires were delivered to the teachers and the students of Junior High schools in Surabaya, Indonesia. Likert scales were used to measure the obtained data. The study revealed that both teachers and students tried hard to prepare classroom tests. Passing classroom tests seemed to be the priority rather than the learning objectives themselves. Exercises for classroom test were therefore mostly given to the students. The materials learned by the students were mostly those students believed or predicted to be the materials for the tests. To some extents thus classroom tests may have both negative as well as positive effects Key Words: Washback Effect, Classroom Tests, Necessary and Unnecessary Decisions.